Experiencia de los profesionales contables en la implementación de las NIIF en México (2015)
The dynamism of the global economy , internationalization of enterprises, the development of securities markets, technological improvement , increased information flow and processing of regulatory bodies , make economic globalization creates the need for rules international and, therefore , to be part of the bonding process whatever way you prefer : adoption , adaptation or other , as if any. The key to this process is given reason is that it is essential for the market to handle financial information that meets the characteristics of comparability, transparency and drivability. That is why applying Internationals Financial Reporting Standards - IFRS today for accounting professionals Mexico is a key issue to remain or become competitive.